PENGARUH PERBEDAAN PANDANGAN DAN INTERPRETASI KONSEP DISTRIBUTIF JUSTICE DALAM BISNIS PERBANKAN - Lestari, Imas Septia; Hasbi, M. Zidny Nafi' (IJMA (Indonesian Journal of Management and Accounting), 2021)
The differences in views and interpretations related to the concept of distributive justice in banking business in Indonesia can have various impacts on the sustainability and stability of banking business, as well as public trust in the banking sector. The purpose of this research is to identify the differences in views and interpretations related to the concept of distributive justice in banking business in Indonesia and its impact. This research was conducted using literature study and case study methods. The results of the research show that the differences in views and interpretations related to the concept of distributive justice in banking business in Indonesia can cause conflicts among the parties involved, injustice in the distribution of profits or risk burdens, a decrease in public trust in banking, and disturbance of the stability of banking business. Based on the results of this research, it is suggested that banks in Indonesia should pay attention to and manage differences in views and interpretations related to the concept of distributive justice in an appropriate way so as not to have a negative impact on banking business.